1979
DOI: 10.3758/bf03332894
|View full text |Cite
|
Sign up to set email alerts
|

Restitution and human sleep: A critical review

Abstract: It is often assumed that human non-REM sleep, especially its apparently more intense form of slow-wave sleep (SWS), is associated with large increases in body restitutional processes, for example, protein synthesis. However, findings from total sleep deprivation appear only to support a brain restitutional role for human sleep and not one of body restitution. Although rises in human growth hormone (hGH) release during SWS might support a body restitutional role, the variety of complex actions of hGH indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Sleep, one of the most fundamental restoration processes, cleans toxic metabolites from the brain, boosts muscle mass, repairs body cells and tissues, and balances hormones that affect a wide range of physiological health markers (Cappuccio, D'Elia, Strazzullo, & Miller, ; Horne, ). The sleep literature has mainly considered physical activity (e.g., exercise) as one of the important sleep hygiene factors (Irish, Kline, Gunn, Buysse, & Hall, ).…”
Section: Weekend Sleep As a Moderatormentioning
confidence: 99%
“…Sleep, one of the most fundamental restoration processes, cleans toxic metabolites from the brain, boosts muscle mass, repairs body cells and tissues, and balances hormones that affect a wide range of physiological health markers (Cappuccio, D'Elia, Strazzullo, & Miller, ; Horne, ). The sleep literature has mainly considered physical activity (e.g., exercise) as one of the important sleep hygiene factors (Irish, Kline, Gunn, Buysse, & Hall, ).…”
Section: Weekend Sleep As a Moderatormentioning
confidence: 99%
“…Administration of melatonin is associated with several metabolic changes in the hypothalamus including alterations in protein synthesis, uptake of neurotransmitters including dopamine, serotonin, norepinephrine, and gamma-amino-butyric acid (GABA), release of neuropeptides, hormones and prostaglandins (Erlich & Apuzzo, 1985). This cascade of neurotransmitters, neuropeptides and neurohormones represents an entire system involved in regenerative and reparative functions acting in synchrony during the period of darkness (Horne, 1979;Datta & King, 1980). It has been suggested that the mechanisms of action of melatonin are mediated through cellular microtubules (Winston et al, 1974).…”
Section: The Pineal Gland and Free Radical Productionmentioning
confidence: 99%
“…We recently noted the emergence of spontaneous abnormal perioral movements in young, drug-naive pinealectomized rats with further augmentation of these movements following administration of haloperidol (Sandyk & Fisher, 1989). 6) There is evidence to suggest that slow-wave sleep (SWS) is associated with significant increases in cerebral restitutional processes (Horne, 1979) with reduction of SWS in subjects of advancing age (Mendelson et al, 1980). 6) There is evidence to suggest that slow-wave sleep (SWS) is associated with significant increases in cerebral restitutional processes (Horne, 1979) with reduction of SWS in subjects of advancing age (Mendelson et al, 1980).…”
Section: ) 9)mentioning
confidence: 99%